EROTICS Global Survey 2017: Sexuality, rights and internet regulations - Palumbo, Mariana (2017)
This survey aimed to nd out how activists working on gender, sexuality and sexual rights use the inter- net in their work. For this purpose, academics, policy makers and independent activists, among others, were invited to answer a series of questions about the role of the internet in their activism and/or per- sonal life, and the dif culties they face in using it freely and fully, considering their experiences re- garding censorship, violence and surveillance online